Electromagnetic shielding nanocrystalline soft magnetic complex and preparation method thereof

By introducing cobalt ferrite into graphene oxide to wrap nanocrystalline alloy powder and coated with insulating resin, a nanocrystalline double-core shielding body with a core structure was prepared, which solved the problem of insufficient performance of existing electromagnetic shielding materials and achieved a more efficient electromagnetic shielding effect.

CN119964921AActive Publication Date: 2025-05-09LONGFENG NEW MATERIALS QIDONG CO LTD +1

Patent Information

Application Number
CN202510432199.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-08
Publication Date
2025-05-09
Estimated Expiration
2045-04-08

AI Technical Summary

Technical Problem

The electromagnetic shielding performance of existing electromagnetic shielding materials is insufficient, and has disadvantages such as large thickness, high density, and application limitations.

Method used

By introducing cobalt ferrate into graphene oxide, the nanocrystalline alloy powder is wrapped, and a nanocrystalline double magnetic core shield with a core-shell structure is prepared, and further coated with an insulating resin to form a dense insulating layer to suppress the eddy current between the magnetic particles.

Benefits of technology

The magnetic loss capability has been improved, the electromagnetic shielding efficiency has been improved, the reflection coefficient has been reduced, and the secondary pollution of electromagnetic radiation has been reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119964921A_ABST
    Figure CN119964921A_ABST
Patent Text Reader

Abstract

The invention discloses an electromagnetic shielding nanocrystalline soft magnetic complex and a preparation method thereof in the technical field of composite materials. The electromagnetic shielding nanocrystalline soft magnetic complex is prepared from the following components in parts by weight: 3-4.5 parts of graphene oxide, 6-7 parts of ferric nitrate nonahydrate, 1.9-2.2 parts of cobalt nitrate hexahydrate, 300-350 parts of nanocrystalline alloy powder and 3-4.2 parts of insulating resin. According to the method, cobalt ferrite is introduced into graphene oxide, nanocrystalline alloy powder is wrapped, a nanocrystalline double-magnetic-core shielding body of a shell-core structure is prepared, the magnetic loss capacity is improved, meanwhile, the shielding body is further wrapped with insulating resin, defects are eliminated, a compact insulating layer is formed, eddy currents among magnetic particles are restrained, and the magnetic loss capacity is improved. The electromagnetic shielding effectiveness is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of composite materials, and specifically refers to an electromagnetic shielding nanocrystalline soft magnetic composite and a preparation method thereof. Background Art

[0002] With the development and popularization of various electronic devices, the electromagnetic pollution generated by electrical equipment has become a threat to the environment and people's health. Electromagnetic shielding refers to reducing the intensity of the electromagnetic field and the radiation of electromagnetic waves through materials or physical barriers, so as to achieve the purpose of reducing electromagnetic interference. Traditional electromagnetic shielding materials have the disadvantages of large thickness, high density, low electromagnetic shielding efficiency, and limited application in the field of electromagnetic shielding. Absorbing materials are a widely used shielding material, which refers to a type of material that effectively reduces electromagnetic radiation when electromagnetic waves are converted into other forms of energy and lost after entering the material, or electromagnetic waves cancel each other out due to interference. Excellent absorbing materials must first have a strong ability to absorb and lose electromagnetic waves. Currently, the commonly used absorbing materials are as follows: ferrite, hydroxy iron material, ceramic material, conductive polymer material, amorphous material, nanocrystalline material; nanocrystalline materials have higher saturation magnetic induction intensity and magnetic permeability than amorphous alloys, lower specific gravity and higher frequency eddy current loss, so they have stronger absorbing ability and wider absorption frequency band.

[0003] The existing technologies currently have the following main problems: the electromagnetic shielding effectiveness of commonly used shielding materials is insufficient. Summary of the invention

[0004] In view of the above situation, in order to overcome the defects of the prior art, the present invention provides an electromagnetic shielding nanocrystalline soft magnetic composite and a preparation method thereof. In order to solve the problem of insufficient electromagnetic shielding effectiveness of commonly used shielding materials, the present invention proposes to introduce cobalt ferrite into graphene oxide and wrap the nanocrystalline alloy powder to prepare a nanocrystalline double-core shielding body with a core-shell structure, thereby achieving an improvement in magnetic loss capacity. At the same time, the shielding body is further coated with an insulating resin to eliminate defects to form a dense insulating layer, thereby suppressing eddy currents between magnetic particles and achieving an improvement in electromagnetic shielding effectiveness.

[0005] In order to achieve the above-mentioned purpose, the technical solution adopted by the present invention is as follows: The present invention proposes an electromagnetic shielding nanocrystalline soft magnetic composite, which is prepared from the following components in parts by weight: 3-4.5 parts of graphene oxide, 6-7 parts of ferric nitrate nonahydrate, 1.9-2.2 parts of cobalt nitrate hexahydrate, 300-350 parts of nanocrystalline alloy powder and 3-4.2 parts of insulating resin.

[0006] Preferably, the insulating resin is epoxy-modified silicone resin, CAS: 67763-03-5, model: SH-023-4.

[0007] Preferably, the nanocrystalline alloy powder is composed of the following components in weight percentage: Mo 1.8-2%, Si 2.5-3%, B 8-8.6%, P 4-4.2%, Cu 1-1.3%, and the balance is Fe and unavoidable impurities;

[0008] Preferably, the method for preparing the nanocrystalline alloy powder specifically comprises the following steps:

[0009] Mo, Si, B, P, Cu and Fe are uniformly mixed and placed in a vacuum of 3×10 -3 Pa and argon protection, arc melting was performed to obtain Fe-Si-BP-Cu-Mo alloy ingots, followed by single-roll stripping to obtain amorphous alloy strips with a thickness of 22 μm. The amorphous alloy strips were vacuum annealed at a vacuum degree of 5×10 -3 Pa, the temperature was raised to 500-550°C at 10°C / min, kept warm for 30 minutes, and then cooled to room temperature. Finally, 8mm steel ball milling balls were used for ball-to-material ratio of 8-10:1 and ball milling at a speed of 300rpm for 10-12 hours to obtain nanocrystalline alloy powder.

[0010] The present invention also provides a method for preparing an electromagnetic shielding nanocrystalline soft magnetic composite, which specifically comprises the following steps:

[0011] S1. Add graphene oxide to deionized water, perform ultrasonic dispersion to obtain a dispersion, add ferric nitrate nonahydrate to deionized water, add cobalt nitrate hexahydrate, stir evenly, and obtain a mixed solution;

[0012] S2, adding the mixed solution obtained in S1 dropwise to the dispersion obtained in S1, adjusting the pH to 12.5, stirring in an oil bath, cooling, and magnetic separation to obtain cobalt ferrite-graphene oxide;

[0013] S3, uniformly mixing the cobalt ferrite-graphene oxide and nanocrystalline alloy powder obtained in S2 to obtain a mixed powder, and ball milling the mixed powder to obtain a nanocrystalline dual-core shielding body;

[0014] S4. Add the nanocrystalline dual-core shielding body obtained in S3 into a 10wt% insulating resin acetone solution, heat at 50°C and stir at 80-100rpm until the powder is dry to obtain an electromagnetic shielding nanocrystalline soft magnetic composite.

[0015] Preferably, in S1, the amount of graphene oxide added to deionized water is 3-4 mg / mL.

[0016] Preferably, in S1, the amount of ferric nitrate nonahydrate added to deionized water is 60-80 mg / mL.

[0017] Preferably, in S2, the oil bath is stirred at a temperature of 80-90°C, a speed of 60-80 rpm, and a time of 4-5 h.

[0018] Preferably, in S3, the ball mill uses 6 mm alumina balls, the ball-to-material ratio is 15-20:1, the rotation speed is 280-300 rpm, and the time is 100-120 min.

[0019] The beneficial effects achieved by the present invention are as follows: by adding Mo, alpha-Fe grains in the nanocrystalline alloy are refined, and the composition is adjusted to obtain a nanocrystalline alloy with good soft magnetic properties; at the same time, cobalt ferrite is introduced into graphene oxide to coat the nanocrystalline alloy powder, an electromagnetic loss composite material is constructed, and a nanocrystalline double-core shielding body with a core-shell structure is obtained, the double-core structure is conducive to generating a synergistic effect through coupling, and the magnetic loss capacity of the material is enhanced, and its heterogeneous structure forms rich dipole polarization and interface polarization to further improve the shielding effect; the nanocrystalline double-core shielding body is secondary coated with an insulating resin to further eliminate defects, form a dense insulating layer, effectively suppress eddy currents between ferromagnetic particles, improve the resistivity of the material, maximize the matching of magnetic properties with dielectric properties, improve the absorptivity of the material, and optimize the impedance matching of the material together with cobalt ferrite-graphene oxide, improve the wave absorption performance, and then reduce the reflection coefficient while improving the total shielding effectiveness, and reduce the pollution caused by secondary reflection. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a result diagram of the reflection coefficient reduction rate of the shielding performance test of Examples 1-3 and Comparative Examples 1-2 of the present invention;

[0021] Figure 2 It is a result diagram of the total shielding effectiveness improvement rate of shielding performance test of Examples 1-3 of the present invention and Comparative Examples 1-2.

[0022] The accompanying drawings are used to provide further understanding of the present invention and constitute a part of the specification. They are used to explain the present invention together with the embodiments of the present invention and do not constitute a limitation of the present invention. DETAILED DESCRIPTION

[0023] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0024] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any methods and materials similar or equivalent to those described herein may be applied to the present invention. The preferred implementation methods and materials described herein are for demonstration purposes only and are not intended to limit the content of this application.

[0025] The experimental methods in the following examples are conventional methods unless otherwise specified; the experimental materials used in the following examples are purchased from commercial channels unless otherwise specified.

[0026] Example 1

[0027] An electromagnetic shielding nanocrystalline soft magnetic composite is prepared from the following components in parts by weight: 3 parts of graphene oxide, 6 parts of ferric nitrate nonahydrate, 1.9 parts of cobalt nitrate hexahydrate, 300 parts of nanocrystalline alloy powder and 3 parts of insulating resin.

[0028] The nanocrystalline alloy powder is composed of the following weight percentage components: Mo1.8%, Si2.5%, B8%, P4%, Cu1%, and the balance is Fe and inevitable impurities;

[0029] The method for preparing nanocrystalline alloy powder specifically comprises the following steps:

[0030] Mo, Si, B, P, Cu and Fe are uniformly mixed and placed in a vacuum of 3×10 -3 Pa and argon protection, arc melting was performed to obtain Fe-Si-BP-Cu-Mo alloy ingots, followed by single-roll stripping to obtain amorphous alloy strips with a thickness of 22 μm. The amorphous alloy strips were vacuum annealed at a vacuum degree of 5×10 -3 Pa, the temperature was raised to 500°C at 10°C / min, kept at that temperature for 30 min, and then cooled to room temperature. Finally, 8mm steel ball milling balls were used, and ball milling was performed at a speed of 300 rpm for 10 h with a ball-to-material ratio of 8:1 to obtain nanocrystalline alloy powder.

[0031] The present invention also provides a method for preparing an electromagnetic shielding nanocrystalline soft magnetic composite, which specifically comprises the following steps:

[0032] S1. Add graphene oxide in an amount of 3 mg / mL to deionized water, and disperse by ultrasonication to obtain a dispersion liquid. Add ferric nitrate nonahydrate in an amount of 60 mg / mL to deionized water, and add cobalt nitrate hexahydrate, and stir to obtain a mixed solution.

[0033] S2, adding the mixed solution obtained in S1 dropwise to the dispersion obtained in S1, adjusting the pH to 12.5, stirring in an oil bath at 80°C and 60 rpm for 4 h, cooling, and magnetically separating to obtain cobalt ferrite-graphene oxide;

[0034] S3, the cobalt ferrite-graphene oxide and nanocrystalline alloy powder obtained in S2 are uniformly mixed to obtain a mixed powder, and the mixed powder is ball-milled with a 6 mm alumina ball at a ball-to-material ratio of 15:1, a rotation speed of 280 rpm, and a time of 100 min to obtain a nanocrystalline dual-core shielding body;

[0035] S4. Add the nanocrystalline dual-core shielding body obtained in S3 into a 10wt% insulating resin acetone solution, heat at 50°C and stir at 80rpm until the powder is dry to obtain an electromagnetic shielding nanocrystalline soft magnetic composite.

[0036] Example 2

[0037] An electromagnetic shielding nanocrystalline soft magnetic composite is prepared from the following components in parts by weight: 4.5 parts of graphene oxide, 7 parts of ferric nitrate nonahydrate, 2.2 parts of cobalt nitrate hexahydrate, 350 parts of nanocrystalline alloy powder and 4.2 parts of insulating resin.

[0038] The nanocrystalline alloy powder is composed of the following weight percentage components: Mo2%, Si3%, B8.6%, P4.2%, Cu1.3%, and the balance is Fe and unavoidable impurities;

[0039] The method for preparing nanocrystalline alloy powder specifically comprises the following steps:

[0040] Mo, Si, B, P, Cu and Fe are uniformly mixed and placed in a vacuum of 3×10 -3 Pa and argon protection, arc melting was performed to obtain Fe-Si-BP-Cu-Mo alloy ingots, followed by single-roll stripping to obtain amorphous alloy strips with a thickness of 22 μm. The amorphous alloy strips were vacuum annealed at a vacuum degree of 5×10 -3 Pa, the temperature was raised to 550°C at 10°C / min, kept at that temperature for 30 min, and then cooled to room temperature. Finally, an 8mm steel ball mill was used for ball-to-material ratio of 10:1 and ball milling at a speed of 300 rpm for 12 h to obtain nanocrystalline alloy powder.

[0041] The present invention also provides a method for preparing an electromagnetic shielding nanocrystalline soft magnetic composite, which specifically comprises the following steps:

[0042] S1. Add graphene oxide in an amount of 4 mg / mL to deionized water, and disperse by ultrasonication to obtain a dispersion liquid. Add ferric nitrate nonahydrate to deionized water in an amount of 80 mg / mL, and add cobalt nitrate hexahydrate, and stir evenly to obtain a mixed solution.

[0043] S2, adding the mixed solution obtained in S1 dropwise to the dispersion obtained in S1, adjusting the pH to 12.5, stirring at 80 rpm in an oil bath at 90°C for 5 h, cooling, and magnetically separating to obtain cobalt ferrite-graphene oxide;

[0044] S3, the cobalt ferrite-graphene oxide and nanocrystalline alloy powder obtained in S2 are uniformly mixed to obtain a mixed powder, and the mixed powder is ball-milled with a 6 mm alumina ball at a ball-to-material ratio of 20:1, a rotation speed of 300 rpm, and a time of 120 min to obtain a nanocrystalline dual-core shielding body;

[0045] S4. Add the nanocrystalline dual-core shielding body obtained in S3 into a 10wt% insulating resin acetone solution, heat at 50°C and stir at 100rpm until the powder is dry to obtain an electromagnetic shielding nanocrystalline soft magnetic composite.

[0046] Example 3

[0047] An electromagnetic shielding nanocrystalline soft magnetic composite is prepared from the following components in parts by weight: 4 parts of graphene oxide, 6.5 parts of ferric nitrate nonahydrate, 2 parts of cobalt nitrate hexahydrate, 325 parts of nanocrystalline alloy powder and 3.5 parts of insulating resin.

[0048] The nanocrystalline alloy powder is composed of the following components in weight percentage: Mo 1.9%, Si 2.7%, B 8.3%, P 4.1%, Cu 1.2%, and the balance is Fe and unavoidable impurities;

[0049] The method for preparing nanocrystalline alloy powder specifically comprises the following steps:

[0050] Mo, Si, B, P, Cu and Fe are uniformly mixed and placed in a vacuum of 3×10 -3 Pa and argon protection, arc melting was performed to obtain Fe-Si-BP-Cu-Mo alloy ingots, followed by single-roll stripping to obtain amorphous alloy strips with a thickness of 22 μm. The amorphous alloy strips were vacuum annealed at a vacuum degree of 5×10 -3 Pa, the temperature was raised to 525°C at 10°C / min, kept at that temperature for 30 min, and then cooled to room temperature. Finally, an 8mm steel ball mill was used for ball-to-material ratio of 9:1 and ball-to-material ratio at 300 rpm for 11 h to obtain nanocrystalline alloy powder.

[0051] The present invention also provides a method for preparing an electromagnetic shielding nanocrystalline soft magnetic composite, which specifically comprises the following steps:

[0052] S1. Add graphene oxide in an amount of 3.5 mg / mL to deionized water, and disperse by ultrasonication to obtain a dispersion liquid. Add ferric nitrate nonahydrate to deionized water in an amount of 70 mg / mL, and add cobalt nitrate hexahydrate, and stir to obtain a mixed solution.

[0053] S2, adding the mixed solution obtained in S1 dropwise to the dispersion obtained in S1, adjusting the pH to 12.5, stirring in an oil bath at 85°C and 70 rpm for 4.5 h, cooling, and magnetic separation to obtain cobalt ferrite-graphene oxide;

[0054] S3, the cobalt ferrite-graphene oxide and nanocrystalline alloy powder obtained in S2 are uniformly mixed to obtain a mixed powder, and the mixed powder is ball-milled with a 6 mm alumina ball at a ball-to-material ratio of 17:1, a rotation speed of 290 rpm, and a time of 110 min to obtain a nanocrystalline dual-core shielding body;

[0055] S4. Add the nanocrystalline dual-core shielding body obtained in S3 into a 10wt% insulating resin acetone solution, heat at 50°C and stir at 90rpm until the powder is dry to obtain an electromagnetic shielding nanocrystalline soft magnetic composite.

[0056] Comparative Example 1

[0057] This comparative example provides a composite, which differs from Example 1 only in that the components do not contain cobalt ferrite-graphene oxide, and the remaining components and component contents are the same as those in Example 1.

[0058] Comparative Example 2

[0059] This comparative example provides a composite body, which is different from Example 1 only in that the composite body does not contain insulating resin, and the remaining components and component contents are the same as those of Example 1.

[0060] Experimental example

[0061] 1. Shielding performance test

[0062] The materials obtained in Examples 1-3 and Comparative Examples 1-2 and the nanocrystalline alloy powder obtained in Example 1 were uniformly mixed with paraffin wax at a mass ratio of 3:1, and pressed into ring-shaped samples with an inner diameter of 3 mm, an outer diameter of 7 mm, and a thickness of 2 mm using a mold, wherein Examples 1-3 and Comparative Examples 1-2 were experimental groups, and the nanocrystalline alloy powder was a control group. The samples were measured using an AV3629 high-performance microwave integrated vector network analyzer using a coaxial method, and the reflection coefficient and total shielding effectiveness of each group of samples at 10 GHz were taken, and the sample reflection coefficient reduction rate and shielding performance improvement rate were calculated;

[0063] The reflection coefficient reduction rate is calculated using the following formula:

[0064] Reflection coefficient reduction rate = (reflection coefficient of control group - reflection coefficient of experimental group) / reflection coefficient of control group × 100%;

[0065] The total shielding performance improvement rate is calculated using the following formula:

[0066] Total shielding effectiveness improvement rate = (total shielding effectiveness of the experimental group - total shielding effectiveness of the control group) / total shielding effectiveness of the control group × 100%.

[0067] Figure 1This is a result graph of the reflection coefficient reduction rate of shielding performance test of Examples 1-3 and Comparative Example 1-2 of the present invention; as shown in the figure, the reflection coefficient reduction rates of Examples 1-3 and Comparative Example 1-2 are 76.5%, 77.3%, 75.9%, 50.6% and 36.2%, respectively; the reflection coefficient reduction rate of Example 1-3 is significantly higher than that of Comparative Example 1-2, indicating that the use of cobalt ferrite-graphene oxide and insulating resin reduces the reflection coefficient of the material and can effectively reduce the secondary pollution of electromagnetic radiation.

[0068] Figure 2 This is a result graph of the total shielding effectiveness improvement rate of shielding performance tests of Examples 1-3 and Comparative Examples 1-2 of the present invention; as shown in the figure, the total shielding effectiveness improvement rates of Examples 1-3 and Comparative Examples 1-2 are 43.0%, 42.3%, 43.9%, 25.1% and 32.3%, respectively; the total shielding effectiveness improvement rate of Example 1-3 is significantly higher than that of Comparative Examples 1-2, indicating that the use of cobalt ferrite-graphene oxide and insulating resin improves the total shielding effectiveness of the material.

[0069] While the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that many changes, modifications, substitutions and variations can be made to the embodiments without departing from the principles and spirit of the invention.

[0070] The present invention and its implementation methods are described above, which is not restrictive. The drawings are only one of the implementation methods of the present invention, and the actual application is not limited thereto. In short, if ordinary technicians in the field are inspired by it and design methods and embodiments similar to the technical solution without creativity without departing from the purpose of the invention, they should all fall within the protection scope of the present invention.

Claims

1. An electromagnetic shielding nanocrystalline soft magnetic composite, characterized in that: The invention is prepared from the following components in parts by weight: 3-4.5 parts of graphene oxide, 6-7 parts of ferric nitrate nonahydrate, 1.9-2.2 parts of cobalt nitrate hexahydrate, 300-350 parts of nanocrystalline alloy powder and 3-4.2 parts of insulating resin; The nanocrystalline alloy powder is composed of the following components in weight percentage: Mo1.8-2%, Si2.5-3%, B8-8.6%, P4-4.2%, Cu1-1.3%, the balance is Fe and unavoidable impurities; The method for preparing the nanocrystalline alloy powder specifically comprises the following steps: Mo, Si, B, P, Cu and Fe are uniformly mixed and placed in a vacuum of 3×10 -3 Pa and argon protection, arc melting was performed to obtain Fe-Si-BP-Cu-Mo alloy ingots, followed by single-roll stripping to obtain amorphous alloy strips with a thickness of 22 μm. The amorphous alloy strips were vacuum annealed at a vacuum degree of 5×10 -3 Pa, the temperature was raised to 500-550°C at 10°C / min, kept at that temperature for 30 minutes, cooled to room temperature, and finally, 8mm steel ball milling was performed for 10-12 hours at a ball-to-material ratio of 8-10:1 and a speed of 300 rpm to obtain nanocrystalline alloy powder; The insulating resin is epoxy-modified silicone resin, CAS: 67763-03-5, model: SH-023-4.

2. A method for preparing the electromagnetic shielding nanocrystalline soft magnetic composite according to claim 1, characterized in that: The specific steps include: S1. Add graphene oxide to deionized water, perform ultrasonic dispersion to obtain a dispersion, add ferric nitrate nonahydrate to deionized water, add cobalt nitrate hexahydrate, stir evenly, and obtain a mixed solution; S2, adding the mixed solution obtained in S1 dropwise to the dispersion obtained in S1, adjusting the pH to 12.5, stirring in an oil bath, cooling, and magnetic separation to obtain cobalt ferrite-graphene oxide; S3, uniformly mixing the cobalt ferrite-graphene oxide and nanocrystalline alloy powder obtained in S2 to obtain a mixed powder, and ball milling the mixed powder to obtain a nanocrystalline dual-core shielding body; S4. Add the nanocrystalline dual-core shielding body obtained in S3 into a 10wt% insulating resin acetone solution, heat at 50°C and stir at 80-100rpm until the powder is dry to obtain an electromagnetic shielding nanocrystalline soft magnetic composite.

3. The method for preparing the electromagnetic shielding nanocrystalline soft magnetic composite according to claim 2, characterized in that: In S1, the graphene oxide is added in an amount of 3-4 mg / mL in deionized water.

4. The method for preparing the electromagnetic shielding nanocrystalline soft magnetic composite according to claim 3, characterized in that: In S1, the amount of ferric nitrate nonahydrate added to deionized water is 60-80 mg / mL.

5. The method for preparing the electromagnetic shielding nanocrystalline soft magnetic composite according to claim 4, characterized in that: In S2, the oil bath is stirred at a temperature of 80-90°C, a speed of 60-80 rpm, and a time of 4-5 h.

6. The method for preparing the electromagnetic shielding nanocrystalline soft magnetic composite according to claim 5, characterized in that: In S3, the ball mill uses 6 mm alumina balls, a ball-to-material ratio of 15-20:1, a rotation speed of 280-300 rpm, and a time of 100-120 min.

Citation Information

Patent Citations

  • Electromagnetic shielding material and nano-grade composite material thereof, and preparation methods thereof

    CN105315963A

  • Automatic offcut collecting device of nanocrystalline strip precision shearing machine

    CN114289773A

  • High-frequency transformer nanocrystalline magnetic core material and preparation method thereof

    CN117809925A

Cited By

  • Weather-proof magnetic material for mutual inductor and preparation method thereof

    CN121617767A

  • Weather-resistant magnetic material for a mutual inductor and method for manufacturing the same

    CN121617767B